DEEP LEARNING BASED PREDICTION MODEL FOR COURSE REGISTRATION SYSTEM - T.M.Nithya, K.S.Guruprakash, L.Amudha (International Journal of Advanced Science and Technology, 2020)
Nowadays in any educational system, selecting course by students according to their need is a challenging task. This paper proposed deep learning approach to predict the courses for the student according to their cutoff marks. The cutoff mark of student is calculated for this course prediction which analyzes the accurate course to choose for their college education. Choosing the appropriate course in any educational institution with infrastructure facilities is the major drawback in the existing system. The existing system will only give the information about the institutions. To overcome the anomalies of the existing system this system proposes the effective course registration system using deep learning based prediction model. The major technique used to predict the course is Decision Tree Algorithm. This algorithm comes under the Deep Learning Technique which comes under Artificial Intelligences that will process the cutoff mark of the student to know about the Science and engineering colleges. This algorithm will analyze the uploaded dataset of the various courses in the colleges and the facility that are providing. The student will initially register their details before logging in to the website. This application will filter the data based on cutoff mark when the student login to the homepage. This will sort out the course information on basis of their cutoff marks. The advantage of the proposed system is that the student can choose the course that they need to study with the accurate predicted data. The Arts and Engineering College are uploading the detail in admin. The BE course are CS, ECE AND EEE are available in course prediction